2012
DOI: 10.1253/circj.cj-11-1259
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Waist Circumference and Risk of All-Cause and Cardiovascular Mortality

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp ecently, a prospective study in more than 1 million Asian subjects has confirmed that there is a U-shaped association between body mass index (BMI) and the risk of death from cancer, cardiovascular disease (CVD), and other causes. 1 But previous epidemiological studies in Japan suggested that increased BMI was unlikely to influence mortality risk, 2,3 whereas a lower BMI or weight loss markedly raised this risk. 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
12
12
0
1
Order By: Relevance
“…Studies using other obesity measures may have yielded different results. 54 Also, this was not a systematic review. Information provided here may not be thorough.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using other obesity measures may have yielded different results. 54 Also, this was not a systematic review. Information provided here may not be thorough.…”
Section: Discussionmentioning
confidence: 99%
“…Third, besides CKD, new biomarkers that can predict the CHD risk are emerging [55][56][57] . However, our study could not access their importance as have other existing prediction tools for Japanese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…9, 10 It is well-recognized that gender differences exist in the prevalence and levels of these CV diseases and risk factors. [11][12][13][14][15][16][17][18][19][20][21][22] Despite accumulating data, there is still no evidence on how gender influences the effects of exercise training with body weight (BW) loss on hsCRP levels. A meta-analysis study demonstrated the effects of aerobic exercise on CRP, 23 but did not present separate data for exercise-derived CRP lowering in each gender.…”
Section: Subjectsmentioning
confidence: 99%